The complete mitochondrial genome of Dendrodoris krusensternii (Gastropoda, Nudibranchia, Dendrodorididae) from South Korea - Seunghyun Lee; Seongjun Bae (Mitochondrial DNA. Part B. Resources)
The complete mitochondrial genome sequence of Dendrodoris krusensternii (J. E. Gray, 1850) was determined using next-generation sequencing. The complete mitochondrial genome of D. krusensternii is 14,361 bp long, comprising 13 genes, including 13 protein-coding genes (PCGs), 22 transfer RNAs, and two ribosomal RNAs. The nucleotide composition was estimated: 28.7% A, 14.8% C, 19.6% G, and 36.9% T. Phylogenetic analysis was performed using the maximum likelihood method (including 13 PCGs). D. krusensternii is related to the Phyllidiidae (superfamily Phyllidioidea), suggesting a distinct phylogenetic placement within Nudibranchia. This study represents a genomic resource, contributing to molecular studies on the evolution of the Dendrodorididae.